Antibacterial Effects of Brown Algae Extracts of Cystoseira Sp. Collected From Tukra Beach, Mediterranean Sea Coast of Libya - Leibirsh, Sumaia F.; Alteerah, Munay A.; Godeh, Masoud M. (International Journal of Scientific Research in Biological Sciences, 2020)
Two species of brown algae Cystoseira compressa and Cystoseira crinita were studied in this project collected from Mediterranean coast of Tukra beach and that was in order to study their inhibition effects on growth of five different species of bacteria (Staphylococcus aureus, Streptococcus pyogenes, Pseudomonas aeruginosa, Klebsiella pneumonia, and Escherichia coli). Five different organic solvents (ethanol, methanol, acetone, ethyl acetate and hexane) were used with both algal species and the bacteria species. Discs of the antibiotic Azithromycin 15 were used as a positive control and dimethyl sulfoxide (DMSO) as a negative control. Nutrient Agar was used to reactivate colonies of bacteria that were used in this study and Muller Hinton (M.H) media was used for the sensitivity test. Well diffusion method was also used in the sensitivity test for both species of Cystoseira which were extracted by applying a cold extraction method. Both Cystoseira spp. showed vary inhibition effects on gram-positive bacteria. aureus and S. pyogenes. Highest inhibition zones were found in colonies of S. aureus and S. pyogenes by using of Cystoseira compressa ethanol extracts. Extracts of both species of Cystoseira had no inhibition effect on gram-negative bacteria